Adding fuel to the fire? Revegetation influences wildfire size and intensity. (1st March 2015) - Collins, L.; Penman, T.D.; Price, O.F.; Bradstock, R.A.
Abstract: The regrowth of woody vegetation in cleared landscapes (i.e. revegetation) has the potential to dramatically alter the spatial characteristics of vegetation and fuels, which will potentially alter fire characteristics. Understanding how revegetation alters fire size and intensity will be critical in determining the social and environmental value of revegetation. We used simulation modelling to examine (i) whether increasing native woody vegetation extent across landscapes cleared for pasture (i.e. revegetation) affects fire size and median fireline intensity and (ii) whether fuel load in the pasture matrix, the initial extent of land clearing and weather conditions during a fire alter the direction and/or magnitude of the relationships between revegetation and fire size or intensity. Simulations revealed that fire size and intensity were altered by increasing woody vegetation extent, though the direction of change was dependent upon landscape context. Increased woody vegetation extent led to (i) increased fire size in landscapes with low pasture fuel load (2 t ha −1 ) regardless of the extent of land clearing, (ii) decreased fire size in highly cleared landscapes with moderate (4.5 t ha −1 ) and high (7 t ha −1 ) pasture fuel load, and (iii) little change to fire size in landscapes subjected to low levels of clearing when pasture fuel load was moderate or high. Similar patterns were observed for fireline intensity. The magnitude of change in fire size and intensity was greatest under extreme fire weather conditions. Revegetation rarely increased median fireline intensity beyond suppressible levels (i.e. 4000 kW m −1 ), with fire weather and pasture fuel load being the main determinants of suppression potential. Our findings show that the response of fire size and intensity to revegetation will depend on landscape scale pasture management. Highlights: Woody regrowth in cleared landscapes (revegetation) may affect fire regimes. We use simulations to model the effect revegetation has on fire across landscapes. When pasture biomass was low fire size increased with revegetation. Under high pasture biomass fire size was decreased or unchanged by revegetation. The response of fire intensity to revegetation was similar to that of fire size.